Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1139/l10-126
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on the effect of longitudinal reinforcement on shear strength of fibre reinforced polymer reinforced concrete beams

Abstract: The shear design equation of CSA S806-02 does not consider the effect of the axial stiffness of the reinforcing bars for beams with effective depth greater than 300 mm. This paper examines the shear strength of such beams without stirrups. A total of 16 beams reinforced with GFRP, CFRP, and steel bars were tested under four-point monotonic loading. The test results were analyzed and compared with the predictions of CSA S806-02 shear design equation. It was observed that the conservatism of CSA S806-02 predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 3 publications
0
20
0
1
Order By: Relevance
“…Shear keys are typically unreinforced, and unreinforced concrete is poor in tension. When mixing fibers such as steel or glass fibers into concrete constituent, tensile strength of concrete as well as shear capacity of monolithic beams can be enhanced [5][6][7][8][9][10]. This paper presents an attempt to improve the shear capacity of dry joints by adding steel fiber and glass fiber into concrete mixture.…”
Section: Introductionmentioning
confidence: 99%
“…Shear keys are typically unreinforced, and unreinforced concrete is poor in tension. When mixing fibers such as steel or glass fibers into concrete constituent, tensile strength of concrete as well as shear capacity of monolithic beams can be enhanced [5][6][7][8][9][10]. This paper presents an attempt to improve the shear capacity of dry joints by adding steel fiber and glass fiber into concrete mixture.…”
Section: Introductionmentioning
confidence: 99%
“…ACI 440.1R-03 guidelines assumed a linear relationship between concrete shear strength and the modulus of elasticity of FRP bar [32], but most of the research shows a cubic root relationship between them [11, 12, 15-19, 22, 26] and some others assumed a square root relationship (CSA S6-06 [36], CNR DT 203 [26], and ISIS-M03-01 [24] design manual). Concrete shear strength is usually taken to be proportional to c to the power of 0.5 [21,24,27,32,37] and this study also found c to the power of 0.5 as appropriate to predicting good result. Nehdi et al [14,20] used c to the power of 0.23 and 0.3 in the consecutive study.…”
Section: Modulus Of Elasticity Of Frp Bar ( )mentioning
confidence: 57%
“…Kara [16] showed good result with a power of (1/9) for / ratio. Razaqpur et al [17] and Alam and Hussein [18] suggest that ( / ) to the power of 0.3 is proportional to the concrete shear strength. Wegian and Abdalla [19] used ( / ) to the power of (1/3) for their study.…”
Section: Shear Span To Depth Ratio ( / )mentioning
confidence: 99%
“…Alam et al [ 17 ] studied the shear strength of FRP reinforced members without transverse reinforcement and reported that the normalized shear strength increased linearly with the cube root of the axial stiffness of the reinforcing bars. However, there were similar results for the shear strength of FRP reinforced elements where it was proportional to the axial stiffness of the longitudinal reinforcement obtained by Alam et al [ 17 ], El-Sayed et al [ 18 , 19 ], and Razaqpur et al [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alam et al [ 17 ] studied the shear strength of FRP reinforced members without transverse reinforcement and reported that the normalized shear strength increased linearly with the cube root of the axial stiffness of the reinforcing bars. However, there were similar results for the shear strength of FRP reinforced elements where it was proportional to the axial stiffness of the longitudinal reinforcement obtained by Alam et al [ 17 ], El-Sayed et al [ 18 , 19 ], and Razaqpur et al [ 20 ]. Hence, the conclusion that the shear strength was proportional to the amount of longitudinal reinforcement was reached by Alkhrdaji et al [ 21 ], and the effect of the reinforcement stiffness and amount of reinforcement on the shear strength of FRP elements, despite no significant influence of the longitudinal reinforcement ratio on the shear strength, was observed by Yost et al [ 22 ].…”
Section: Introductionmentioning
confidence: 99%